Metodologías activas para el desarrollo cognitivo en el aprendizaje de los niños del subnivel de Educación Preparatoria. - Rodríguez Castellano, Adriana Elizabeth (2020)
The present research paper was oriented to the deep inquiry into the problem of the efficient level of cognitive development in students of the sub-level of Preparatory Education, which is impaired by the lack of knowledge of teaching activities that focus on the development of cognitive skills of attention, perception, memory and thinking. The general objective established for the development of research was to achieve cognitive development in children so that the level of attention increases and retains in its memory the previous knowledge through active methodologies of the students of the sub-level of preparatory education of the School of Basic Education "Isidro Ayora" Methodological design was framed in the qualitative approach in the feasible project modality , an interview was applied to the Area Coordinator, a student observation sheet, a teacher survey and a survey of parents, to diagnose the situation of the problem, where results were obtained that showed deficiencies in terms of cognitive development, a large percentage of students do not have an adequate level of attention within the teaching-learning process , a high percentage of students who do not remember the contents taught in the previous class, as well as a large percentage of parents who consider their children's learning level to be regular and can therefore be improved. This allowed to develop a proposal with 8 active methodologies focused on cognitive development, learning, selective attention, divided, alternating, sustained; visual, auditory, tactile perception; short- and long term episodic memory; thought and creativit